Kongsberg Vision Meeting Abstracts 2022 - Baraas, Rigmor C. (Scandinavian Journal of Optometry and Visual Science, 2022)
Kongsberg Vision Meeting 2022: Abstracts Kongsberg Vision Meeting was held at the University of South-Eastern Norway in Kongsberg, for the 14th time, on November 7–9, 2022. The meeting was organised as a three-day meeting with a lighting design dayfollowed by two clinical optometry and vision research days. Rigmor C. Baraas, Sylvia Pont, Helle K. Falkenberg, Vibeke Sundling, Tove Lise Morisbakk, Gro Horgen Vikesdal, Lotte-Guri B. Steen, Trine Langaas, Randi Mork and Are Røysamb organised the three-day meeting. The theme this year was Light & Vision in a Public Health Perspective. Keynote speakers for the lighting design day was Wout van Bommel and for the research day were Bruce Moore and Vibeke Sundling. Lee Turner from the Department for Education, His Majesty’s Government, UK and Mark Mon-Williams, University of Leeds and Bradford Institute of Health Research, UK held a special session on the randomized control trial (RCT) Glasses-in-Classes, a project run in state-funded primary schools based in the Metropolitan area of Bradford (UK) to ensure that children who need eyeglasses both have access to an eye examination as well as two pairs of glasses. Teachers are informed and trained to ensure children who have been prescribed with glasses wear them at school, and that their spare pair is available if they attend school without their home pair. Preliminary results from the RCT show that wearing eyeglasses over one school year significantly improves reading and literacy skills when a child who need eyeglasses wears them as compared with those who need eyeglasses, but do not wear them. The abstracts from the other invited and contributed talks on the different days are presented in the order they were given. Received October 1, 2022. Accepted November 1, 2022.